Up to half of patients diagnosed with chronic lymphocytic leukemia in México may not require treatment - Cruz-Mora, Antonio; Murrieta-Alvarez, Iván; Olivares-Gazca, Juan Carlos; León-Peña, Andrés; Cantero-Fortiz, Yahveth; García-Navarrete, Yarely Itzayana; Sánchez-Valledor, Luisa Fernanda; Khalaf, Dina; Ruiz-Delgado, Guillermo José; Ruiz-Argüelles, Guillermo José (Hematology (Luxembourg), 2020)
Introduction: Although therapeutic choices for patients with chronic lymphocytic leukemia (CLL) were once limited, treatment of this disease has vastly improved in the last decades. Patients and methods: Consecutive CLL patients diagnosed in a single institution were analyzed. Treatment was withheld in persons with CLL Rai stage 0 or 1, until progression and in persons with stages 2-4, with a negative expression of ZAP-70 until progression. Between 1983 and 1991, patients were give chlorambucil and prednisone (CP); after 1991 fludarabine and cyclophosphamide (FC) and after 1998, rituximab and FC (FCR). Results: 98 patients with CLL were identified; 49 were followed for >3 months. 21 persons (43%) did not require treatment nor progressed; 14 received CP, 6 FC, 7 FCR and one rituximab. Median overall survival (OS) has not been reached, being above 247 months; median OS for patients given CP was 115 months, for FC above 132 months and for FCR above 136 months (p > 0.5). Conclusion: CLL seems to be less aggressive in Mexican mestizos than in Caucasians; 43% of patients do not need treatment at all.